Answer:
[tex]y_2=xe^{2x}[/tex]
Step-by-step explanation:
We have the differential equation y'' − 4y' + 4y = 0,
so we get that is p(x)=-4.
We use the formula:
[tex]y_2=y_1(x)\int \frac{e^{-\int p(x)\, dx}}{y^2_1(x)}\, dx[/tex]
We have that:
[tex]y_1=e^{2x}[/tex]
we calculate:
[tex]y_2=y_1(x)\int \frac{e^{-\int p(x)\, dx}}{y^2_1(x)}\, dx\\\\y_2=e^{2x}\int \frac{e^{4\int 1\, dx}}{(e^{2x})^2}\, dx\\\\y_2=e^{2x}\int \frac{e^{4x}}{e^{4x}}\, dx\\\\y_2=e^{2x}\int 1\, dx\\\\y_2=xe^{2x}[/tex]
So, we get that
[tex]y_2=xe^{2x}[/tex]